Dampak Body Shaming Terhadap Kepercayaan Diri Remaja - Febiola, Angela Lisky; Fitriani, wahidah (Batanang : Jurnal Psikologi, 2023)
┬áBody shaming is a case that often occurs in social circles, especially in the association of women and most of the victims are also women. Victims of body shaming often feel distant, lonely, and insecure. This insult is everywhere: ridicule, swearing, gossip, and clowns. Verbal abuse is when a parent, friend or person around them uses derogatory, haunting or negatively labeled words to crystallize all these insults into one person.Therefore, the effect experienced is a relatively low selfconfidence, which also affects aspects of personal life. In this study, the researcher uses phenomenological methods and grounding theory, a type of qualitative research in which the researcher uses participant observation to collect data and determine important phenomena. in participants' life experiences victims of body shaming see themselves only as a negative message. This condition refers to thinking in which other people judge themselves as better or worse. He also perceives that others see him as inferior, thus leading to low self-esteem.cause feelings of insecurity and comfort. The conclusion of this study is that there is an effect of body shaming on adolescent self-esteem. Individuals who have experienced body shaming treatment feel ashamed and inferior to other friends because they feel they cannot meet the beauty standards that are developing in society and this makes a body shaming victim motivated to experience changes to themselves to be accepted by society, even though they have made changes, there are still sensitive matters when it comes to her body.┬áKeywords: ┬áBody shaming, Self-confidence,Bullying.